(3Jbhje HQGeL GdJfejI GdegfjI deYdei Yde GdfaS HGdeQMdI GdKGfhjI CKfGA GdNOeI ai eUQ ai VhA GdGJLGgGJ GdYGdejI hGdGMJjGLGJ GdeMdjI (B/ s - (3OfjG eMeO aDGO SGdes; (3EdgGe YHOGdMejO aQL (B: s; (3TGOjI YHOGdMdje JeGe (B: s ((3GdbGgQI (B: s (3OfjG eMeO aDGO SGde (B: s, 2010)
(3gOa GdHMK dJbhje HQGeL GdJfejI GdegfjI deYdei Yde GdfaS HGdeQMdI GdKGfhjI hGdhbha Ydi fbGW GdbhI hGdVYa ai GdHQGeL GdebOeI hGSJNOe GdHMK GdefgL GdhUai hGSJNOe GdGSJHjGfI cCOGI ddOQGSI dJYQa BQGA GdeYdejf GdeJOQHjf hGdeOQHjf ai GdHQGeL GdebOeI HdZJ GdYjfI (B(60 (3eYdeG dYde GdfaS (B) ( 20(3eOQHG (B) (3hJhUd GdHMK ai fJGFLI Edi hLhO bUhQ ai HQGeL GdJfejI GdegfjI GdebOeI hbUhQ ai GaJJGMgG Ydi GdGJLGgGJ GdYGdejI ddJfejI GdegfjIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ GdJQHhjI (B- (3bSe GdefGgL hWQb GdJOQjSs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCJLGgGJ GdYGdejIs; (3HQGeL GdJfejI GdegfjI s; (3Jbhjes